English English - Suprayitno, Aryadimas; Rusgianto, Sulistya; Arifin, Samsul (Jurnal Ekonomika dan Bisnis Islam, 2024)
Poverty is a problem in developing countries resulting from the dualism of modern sector development that provides limited employment opportunities. The handling of the problem can be done by multidimensional policies based on economic and non-economic aspects. This study aims to analyze the effect of digitalization, foreign investment, education, economic growth, and Islamic banks partially on poverty in Indonesia. The object of observation is 33 provinces in Indonesia over 10 years from 2012 to 2021 and processed with static panel regression. The results showed that digitalization, foreign direct investment, and education have a negative significant effect on poverty. On the other hand, Islamic bank has negative and insignificant effect on poverty. Economic growth has a positive and significant effect on poverty. The implication of this research is that strengthening digital infrastructure and expanding access to education can have a positive impact on investment, while economic growth can in turn reduce poverty. This research contributes to providing recommendations on how strengthening digital infrastructure and wider access to education can reduce poverty in Indonesia.